2021
DOI: 10.1016/j.jinf.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Outcomes of 1-year post-discharge care trajectories of patients admitted with infection due to antibiotic-resistant bacteria

Abstract: Background: The impact of antibiotic resistance (AMR) on initial hospital management has been extensively studied but its consequences after hospital discharge remain largely unknown. We aimed to analyze hospital care trajectories, cumulative length of hospital stays (c-LOS) and associated costs of care over a 1-year period after hospitalization with incident AMR infection. Method: All incident bacterial infection-related hospitalizations occurring from January 1, 2015, to December 31, 2015 and recorded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Biaya perawatan pasien dengan infeksi yang disebabkan oleh organisme yang telah resisten lebih besar US $ 6.000-30.000 dibanding pasien dengan infeksi bukan disebabkan oleh organisme yang resisten terhadap antibiotik (Maragakis et al, 2008). Lama waktu perawatan di rumah sakit pada pasien infeksi dengan bakteri resisten meningkat sebanyak 20,4 hari (Touat et al, 2021). Melihat berbagai dampak buruk yang terjadi akibat resistensi antibiotik, maka perlu dilakukan upaya untuk mengendalikan kejadian resistensi antibiotik.…”
Section: Pendahuluanunclassified
“…Biaya perawatan pasien dengan infeksi yang disebabkan oleh organisme yang telah resisten lebih besar US $ 6.000-30.000 dibanding pasien dengan infeksi bukan disebabkan oleh organisme yang resisten terhadap antibiotik (Maragakis et al, 2008). Lama waktu perawatan di rumah sakit pada pasien infeksi dengan bakteri resisten meningkat sebanyak 20,4 hari (Touat et al, 2021). Melihat berbagai dampak buruk yang terjadi akibat resistensi antibiotik, maka perlu dilakukan upaya untuk mengendalikan kejadian resistensi antibiotik.…”
Section: Pendahuluanunclassified
“…Resistant infections worsen delicate patient states and antimicrobial resistance raises fatality rates. [1] In a recent survey, the Organization for Economic Cooperation and Development (OECD) estimated that 2.4 million humans in Europe, North America, and Australia would die from diseases with resistant bacteria in the next 30 years. [2] Another study revealed that resistance to drugs Acinetobacter baumannii (A. baumannii) strains were shown to be typically resistant to ordinary β-lactamase antibiotics, with or without the inclusion of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial resistance (AMR) is one of the crucial problems in the treatment of bacterial infections. Resistant infections worsen delicate patient states and antimicrobial resistance raises fatality rates [1] . In a recent survey, the Organization for Economic Co‐operation and Development (OECD) estimated that 2.4 million humans in Europe, North America, and Australia would die from diseases with resistant bacteria in the next 30 years [2] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In many countries, drug-resistant infections have been associated with longer hospital stays, increased morbidity and mortality, and higher healthcare costs. [4][5][6] Despite the challenge, antimicrobial stewardship (AMS) solutions are not widespread. [7][8][9][10] Standard treatment guidelines (STGs) are one important tool in ensuring high quality clinical care and prudent antimicrobial use, alongside other AMS and educational efforts.…”
Section: Introductionmentioning
confidence: 99%